The Role of PPKN Teachers in Strengthening Student Character as an Effort to Prevent Bullying At SMP Negeri 5 Ulunoyo in the 2022/2023 Academic Year - Albertus Arozato Laia; Berkat Persada Lase; Syukur Kasieli Hulu (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the role of Civics teachers in strengthening student character as an effort to prevent bullying and to find out the obstacles faced by Civics teachers in strengthening student character as an effort to prevent bullying. This research takes a descriptive approach using qualitative methods. The purpose of using a descriptive approach is to reveal or obtain information from research data thoroughly, broadly and deeply. Data collection techniques are interviews, observation, and documentation. The results of the research and discussion concluded that: first, the role of Civics teachers in strengthening student character is to take a good approach to students by getting along with students so that students are not afraid to convey what their complaints are and provide moral encouragement so that students can accept and feel motivated and can avoid bad behavior. Second, what characters are strengthened by Civics teachers in preventing bullying is the character of tolerance where tolerance is respecting differences, and still giving advice to students on how to establish good communication, discipline, for example, obeying the dress code, arriving on time when entering school to obey the rules set by the teacher at school, as well as honest character and as well as getting used to educated participants staring directed at positive activities so as to avoid things related to bullying. Third, the obstacles faced in linking student character as an effort to prevent bullying are the lack of self-confidence of these students, for example in terms of speaking, interacting between students is difficult for the teacher to guess because some students prioritize silence and do not talk much, and vary in terms of receiving learning in equipping themselves to get learning, and do not want to listen or ignore what the teacher says.